2019
DOI: 10.21597/jist.579326
|View full text |Cite
|
Sign up to set email alerts
|

Batman Barajı’nda (Türkiye) Yaşayan Chondrostoma regium’un (Heckel, 1843) Bazı Dokularında Ağır Metallerin Mevsimsel Değişimi

Abstract: In this study, it was aimed to investigate seasonal changes in levels of Chromium (Cr), Manganese (Mn), Iron (Fe), Cobalt (Co), Nickel (Ni), Copper (Cu), Zinc (Zn), Cadmium (Cd) and Lead (Pb) in liver, gill and muscle tissues of Chondrostoma regium from Batman Dam. Inductively coupled plasma mass spectrometry (ICP-MS) was used to analyze heavy metal concentration levels in the fish. The metal concentrations in the same tissues of samples taken from Batman Dam were slightly variable. Among the metals that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…The research by Kaya and Türkoğlu [25] revealed that C. gibelio from Keban Dam Lake had significantly lower As, Mn, Ni, and Cd levels in their tissue when compared with this research but had higher levels of Cr and Co. Likewise, the average Mn, Co, Ni, Cu, and Cd (excluding Cr) found in Chondrostoma regium tissue from the Batman Dam in Turkey by Kaçar and Karadede-Akın [26] were significantly lower compared to our research. In this research, the average Cu, Mn, and Ni concentrations in the muscle tissue samples of C. gibelio were greater than those for Tor grypus in Atatürk Dam Lake (Turkey) but Cr and Co levels were lower [27].…”
Section: Resultscontrasting
confidence: 61%
“…The research by Kaya and Türkoğlu [25] revealed that C. gibelio from Keban Dam Lake had significantly lower As, Mn, Ni, and Cd levels in their tissue when compared with this research but had higher levels of Cr and Co. Likewise, the average Mn, Co, Ni, Cu, and Cd (excluding Cr) found in Chondrostoma regium tissue from the Batman Dam in Turkey by Kaçar and Karadede-Akın [26] were significantly lower compared to our research. In this research, the average Cu, Mn, and Ni concentrations in the muscle tissue samples of C. gibelio were greater than those for Tor grypus in Atatürk Dam Lake (Turkey) but Cr and Co levels were lower [27].…”
Section: Resultscontrasting
confidence: 61%
“…Similarly, Fe values determined for the muscles in this study are higher than those determined for A. marmid and C. regium collected from the Keban Dam Lake (Çalta and Canpolat 2006). Kaçar and Karadede-Akın (2019) reported the highest concentrations of Fe in the tissues of C. regium from the Batman Dam Lake. Furthermore, metal concentrations in all tissues of C. regium in this study were found to be higher than those reported for C. regium from the Karasu River, Turkey (Aydogan et al 2017).…”
Section: Discussionmentioning
confidence: 97%